2020
DOI: 10.1161/jaha.120.017963
|View full text |Cite
|
Sign up to set email alerts
|

Association of Isolated Diastolic Hypertension Based on the Cutoff Value in the 2017 American College of Cardiology/American Heart Association Blood Pressure Guidelines With Subsequent Cardiovascular Events in the General Population

Abstract: Background The 2017 American College of Cardiology (ACC)/American Heart Association (AHA) guidelines lowered the threshold of blood pressure (BP) for hypertension to 130/80 mm Hg. However, the clinical significance of isolated diastolic hypertension (IDH) according to the cutoff value of the 2017 ACC/AHA guidelines was uncertain. Methods and Results We analyzed the claims database of Japan Medical Data Center (a nationwide epidemiological database). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…The dependability of the diastolic foot and our robust DBP estimation were necessary before performing in-depth analyses with confidence. Although elevated SBP is considered to be the greatest predictor of future cardiovascular risk [ 39 , 40 ], elevated DBP has nonetheless been shown to independently increase the risk of subsequent cardiac events [ 39 , 41 ]. In addition, DBP is a greater contributor to MAP, which in older patients with isolated systolic hypertension, when compared with an equivalent increase in pulse pressure, has been shown to be a comparable independent predictor of both stroke and all-cause mortality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dependability of the diastolic foot and our robust DBP estimation were necessary before performing in-depth analyses with confidence. Although elevated SBP is considered to be the greatest predictor of future cardiovascular risk [ 39 , 40 ], elevated DBP has nonetheless been shown to independently increase the risk of subsequent cardiac events [ 39 , 41 ]. In addition, DBP is a greater contributor to MAP, which in older patients with isolated systolic hypertension, when compared with an equivalent increase in pulse pressure, has been shown to be a comparable independent predictor of both stroke and all-cause mortality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are conflicting results from previous large epidemiological studies on whether the 2017 ACC/AHA guideline‐based IDH is associated with an increased risk of CVD outcomes. 8 , 9 , 14 , 18 , 19 The studies by McEvoy and coworkers 8 in American adults and McGrath and coworkers 14 in the United Kingdom Biobank cohort showed that there was no association between the 2017 ACC/AHA guideline‐defined IDH and an increased risk of CVD outcomes. This conclusions was contrary to our findings, and these differences with our findings might be attributable to the differences in the study population, study design, end points, follow‐up time, and location.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these studies that reported an absence of any association between IDH and CVD outcomes, the following studies showed a significant association between IDH and CVD outcomes. A large‐scale, epidemiological study in Japan 18 showed that IDH as defined by the 2017 ACC/AHA guideline was associated with an increased risk of CVD events. This conclusions is similar to our study results, but the primary end points in our study and theirs were different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependability of the diastolic foot and our robust DBP estimation were necessary before performing in-depth analyses with confidence. Although elevated SBP is considered to be the greatest predictor of future cardiovascular risk [39,40], elevated DBP has nonetheless been shown to independently increase the risk of subsequent cardiac events [39,41]. In addition, DBP is a greater contributor to MAP, which in older patients with isolated systolic hypertension, when compared with an equivalent increase in pulse pressure, has been shown to be a comparable independent predictor of both stroke and all-cause mortality [42].…”
Section: Accurately Estimating Bp In a Diverse Population Using A Multimodal Wearable Devicementioning
confidence: 99%